COVID-19: Falling Apart and Bouncing Back. A Collective Autoethnography Focused on Bioethics Education - Dercon, Katrien; Domaradzki, Mateusz; Elisenberg, Herman; Głos, Aleksandra; Handeland, Ragnhild; Popowicz, Agnieszka; Piasecki, Jan (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
The COVID-19 pandemic disrupted academic life worldwide for students as well as educators. The purpose of this study is to shed light on the collective adversity experienced by international medical students and bioethics educators caused by the COVID-19 pandemic in relation to both personal and academic life. The authors wrote their subjective memoirs and then analyzed them using a collective autoethnography method in order to find the similarities and differences between their experiences. The results reveal some consistent patterns in experience that are captured in two metaphors: Falling apart and Bouncing back. “Falling apart” involves the breakdown of daily lives during the initial stages of the pandemic, shown through subjective quotes contextualized through the authors’ commentary. The consensus is that returning home and the transition to remote education were the two main reasons for the breakdown. “Bouncing back” encompasses the authors’ recovery after the initial breakdown, achieved by acquiring new information about the virus, discovering how to continue their hobbies at home, such as working out or dancing, and learning to adjust exam expectations. At the educational level, the bioethics course, which guided students through the ethical dilemmas of the pandemic, played an important role in the recovery/bouncing back process. For that reason, we report on how it was to learn about and teach this subject during the pandemic, and how bioethics knowledge was applied for better understanding and coping with some of the moral dilemmas related to the pandemic. The study testifies to the importance of bioethics education during a pandemic and explains how this can contribute to shaping the moral resilience of future medical practitioners.